Kepemimpinan Yesaya: Misi Kenabian dalam Mengubah Sejarah Israel - Grecetinovitria Marliana Butar-butar; Fitri Lyli Septiani Sitompul; Dian Sipahutar (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Isaiah, a prophet in the 8th century BC in Jerusalem, has an important role in Jewish and Christian religious traditions. He began receiving divine revelations around 742 BC when the Assyrian Empire expanded its territory westward. Isaiah understood the political and foreign issues facing the Jewish kingdom, including relations with other countries such as Egypt, Ethiopia, and Assyria. Although the reigns of Jeroboam II and Uzziah were marked by economic prosperity, social justice was often overlooked. Isaiah firmly rebukes the rich and officials who oppress the poor, and he calls for the restoration of justice. In addition to being a prophet, Isaiah was also active in political affairs, believing that divine messages should play a role in political decisions. Although his advice was often ignored, he nevertheless warned of the consequences of sin and announced future arrivals promised in prophecy, including the coming of Immanuel. Methodologically, Isaiah received a divine call in the 8th century BC, facing moral and political challenges in Judah, and through that vision and call, he demonstrated faithfulness and the power of faith in conveying divine messages.